Seasonality and trend analysis of tuberculosis in Lahore, Pakistan from 2006 to 2013 - Aasia Khaliq; Syeda Aadila Batool; M. Nawaz Chaudhry (Springer, 2019)
Tuberculosis (TB) is a respiratory infectious disease which shows seasonality. Seasonal variation in TB notifications has been reported in different regions, suggesting that various geographic and demographic factors are involved in seasonality. The study was designed to find out the temporal and seasonal pattern of TB incidence in Lahore, Pakistan from 2006 to 2013 in newly diagnosed pulmonary TB cases. SPSS version 21 software was used for correlation to determine the temporal relationship and time series analysis for seasonal variation. Temperature was found to be significantly associated with TB incidence at the 0.01 level with p = 0.006 and r = 0.477. Autocorrelation function and partial autocorrelation function showed a significant peak at lag 4 suggesting a seasonal component of the TB series. Seasonal adjusted factor showed peak seasonal variation in the second quarter (April-June). The expert modeler predicted the Holt-Winter's additive model as the best fit model for the time series, which exhibits a linear trend with constant (additive) seasonal variations, and the stationary R2 value was found to be 0.693. The forecast shows a declining trend with seasonality. A significant temporal relation with a seasonal pattern and declining trend with variable amplitudes of fluctuation was observed in the incidence of TB.